Disease activity and treatment efficacy using patient-level Psoriasis Area and Severity Index scores from tildrakizumab phase 3 clinical trials. (2nd January 2022) - Gordon, K. B.; Reich, K.; Crowley, J. J.; Korman, N. J.; Murphy, F. T.; Poulin, Y.; Spelman, L.; Yamauchi, P. S.; Mendelsohn, A. M.; Parno, J.; Rozzo, S. J.; Ellis, C. N.
Abstract: Background: It is unclear whether primary efficacy outcomes in plaque psoriasis clinical trials represent residual disease during treatment. Objectives: To evaluate supplementing dichotomous efficacy with residual disease activity. Methods: This post hoc analysis used pooled, patient-level data after tildrakizumab 100 mg ( N  = 616) or placebo ( N  = 309) treatment from reSURFACE 1/2 (NCT01722331/NCT01729754) phase 3 clinical trials of patients with moderate to severe plaque psoriasis. Results: Median baseline Psoriasis Area and Severity Index (PASI) was 17.9 for patients receiving tildrakizumab 100 mg. At Week 12, median PASI was 2.9, whereas dichotomous PASI 90 response rate was 36.9%, and absolute PASI <5.0, <3.0, and <1.0 were 64.0%, 50.8%, and 23.3%, respectively. At Week 28, median PASI was 1.7, whereas PASI 90 response rate was 51.9%, and absolute PASI <5.0, <3.0, and <1.0 were 75.3%, 62.8%, and 38.0%, respectively. Dermatology Life Quality Index and PASI scores were correlated through Week 28 ( r  = 0.51, p  ≤ .0001). Conclusions: Disease activity was more reliably estimated by PASI scores than percentage PASI improvement; this may partially explain efficacy disparities between clinical trials and practice. These results suggest supplementing dichotomous PASI improvement with PASI scores and consideration of patient treatment goals could facilitate clinical decisions.